Saccharomyces cerevisiae oral immunization in mice using multi-antigen of the African swine fever virus elicits a robust immune response - Gao, Shuo; Zuo, Wenfeng; Kang, Chao; Zou, Zhong; Zhang, Kaiqi; Qiu, Jun; Shang, Xiaomin; Li, Jingjing; Zhang, Yuanfeng; Zuo, Qi; Zhao, Ya; Jin, Meilin (Frontiers in Immunology, 2024)
African swine fever virus (ASFV) is one of the most complex viruses. ASFV is a serious threat to the global swine industry because no commercial vaccines against this virus are currently available except in Vietnam. Moreover, ASFV is highly stable in the environment and can survive in water, feed, and aerosols for a long time. ASFV is transmitted through the digestive and respiratory tract. Mucosal immunity is the first line of defense against ASFV. Saccharomyces cerevisiae (SC), which has been certified by the U.S. Food and Drug Administration and has a generally recognized as safe status in the food industry, was used for oral immunization in this study. ASFV antigens were effectively expressed in recombinant SC strains with high DNA copy numbers and stable growth though surface display technology and chromosome engineering (δ-integration). The recombinant SC strains containing eight ASFV antigens—KP177R, E183L, E199L, CP204L, E248R, EP402R, B602L, and B646L— induced strong humoral and mucosal immune responses in mice. There was no antigenic competition, and these antigens induced Th1 and Th2 cellular immune responses. Therefore, the oral immunization strategy using recombinant SC strains containing multiple ASFV antigens demonstrate potential for future testing in swine, including challenge studies to evaluate its efficacy as a vaccine against ASFV.